"Becoming Co-conspiratorial", in "Tiny Coronavirus Stories: 'This misery loves isolation'" - Kathryn Coleman, KC; MacDonald, A (The Arctic Cycle, 2020)
Isolation gives cause to become curious about our personal, environmental and circumstantial contexts; the subsequent actions we enact from in-between these spaces have tangible impact upon the people we encounter and the places we traverse in life. How does our tending to various terrains shape our ways of being in the COVID-19 world? (This is a short collaborative creative writing piece with accompanying digital a/r/tographic piece)